Monoclonal antibodies against influenza viruses: a clinical trials review - Mota, Kenneth Gabriel; Moro, Ana Maria (Frontiers in Immunology, 2025)
The zoonotic influenza viruses cause seasonal epidemics and occasional pandemics, posing a significant public health threat. Transmitted by influenza A and B viruses, they result in 1 billion annual infections, 3–5 million severe cases, and 300,000–500,000 deaths worldwide, with U.S. healthcare costs reaching 87.1 billion yearly. Understanding viral biology is crucial for developing effective treatment and prevention strategies. This review analyzes 27 clinical trials of anti-influenza monoclonal antibodies (mAbs) from ClinicalTrials.gov, assessing their therapeutic and prophylactic potential. Some mAbs target conserved viral regions (e.g., hemagglutinin stem, M2e protein) for broad-spectrum neutralization. MHAA4549A demonstrated a 97.5% reduction in viral load in H3N2 models and showed synergistic effects with oseltamivir in severe cases. However, despite preclinical promise, others, such as VIR-2482 (intramuscular) and MEDI8852, failed in Phase 2 trials. Safety profiles were generally favorable, with mild Emergent Adverse Events (EAEs) (headache, gastrointestinal disturbances). Key challenges include poor mucosal tissue penetration and variable clinical responses. While mAb-oseltamivir combinations accelerated recovery in hospitalized patients, larger cohorts lacked statistical significance. Viral evolution remains a significant hurdle, emphasizing the need to target conserved epitopes. Future strategies may optimize half-life (e.g., Fc modifications in VIR-2482), improve mucosal delivery, and integrate mAbs with vaccines/antivirals. mAbs hold promise for high-risk groups and pandemics but require further engineering to enhance efficacy and overcome biological barriers. Refinements in administration and design could establish monoclonal antibodies (mAbs) as a key tool in the management of influenza.